Securing IoT system Access Control using Blockchain-Based Approach - Mulani, Umar M; Patil, Manoj (International Journal of Intelligent Systems and Applications in Engineering, 2022)
There are many reasons to be concerned about the safety and privacy of the Internet of Things (IoT), given its decentralised design and rapid growth. Controlling who can enter a building is a pressing concern. Centralized systems have low scalability and availability, which could cause a bottleneck in performance. This study introduces a novel approach to controlling the distribution of lightweight, decentralised, secure access management of an Internet of Things (IoT) system by combining a multi-agent system and a blockchain. To protect IoT access control and facilitate secure communication between local IoT devices, the proposed method proposes the development of Blockchain Managers (BCMs). In addition, the innovation enables safe connections between fog nodes, Internet of Things gadgets, and cloud servers.